2008
DOI: 10.1158/0008-5472.can-08-1323
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-7 Inhibits Telomerase Activity, Telomere Maintenance, and Cervical Tumor Growth

Abstract: Telomere maintenance is critical in tumor cell immortalization. Here, we report that the cytokine bone morphogenetic protein-7 (BMP7) inhibits telomerase activity that is required for telomere maintenance in cervical cancer cells. Application of human recombinant BMP7 triggers a repression of the human telomerase reverse transcriptase (hTERT) gene, shortening of telomeres, and hTERT repression-dependent cervical cancer cell death. Continuous treatment of mouse xenograft tumors with BMP7, or silencing the hTERT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…In keeping with this, data from the MTT cell proliferation assay showed no differences in cell viability and proliferation between control and A549 cells. BMP7 has been indicated to act as a mediator/regulator of cell survival and apoptosis in several tumour cell lines (3,(6)(7)(8)13,25,26,27), including prostate cancer cells, colon cancer cells, breast cancer cells and melanoma cells and renal cancer cells. In the present study, our results from the apoptosis assay showed that BMP7 offers no significant protection against apoptosis in the tumour cells transfected with BMP7 in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with this, data from the MTT cell proliferation assay showed no differences in cell viability and proliferation between control and A549 cells. BMP7 has been indicated to act as a mediator/regulator of cell survival and apoptosis in several tumour cell lines (3,(6)(7)(8)13,25,26,27), including prostate cancer cells, colon cancer cells, breast cancer cells and melanoma cells and renal cancer cells. In the present study, our results from the apoptosis assay showed that BMP7 offers no significant protection against apoptosis in the tumour cells transfected with BMP7 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Distant metastasis is an important cause for the poor prognosis. Of the factors related to metastasis, bone morphogenetic proteins (BMPs) have been recently shown to regulate the aggressiveness of cancer cells (1)(2)(3)(4)(5)(6)(7). BMPs are multifunctional signaling molecules belonging to the transforming growth factor-β (TGF-β) superfamily, which play important roles in multiple cellular processes such as cell growth, differentiation, migration and apoptosis in various types of cancer (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Telomere repeat amplification protocol assays and telomere length analysis were performed as previously described (44) with minor modifications (45,46).…”
Section: Methodsmentioning
confidence: 99%
“…Gremlin 1 is also reported to be expressed in cervical cancer compared to normal tissues of the cervix (37). A few studies have investigated the significance of BMPs in cervical cancer (38)(39)(40), however, there are no studies on the clinicopathological significance of Gremlin 1 in cervical cancer nor on the function of Gremlin 1 in CSC-like cells of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%